LANDSLIDE HAZARD ZONATION BASED ON DETERMINISTIC METHOD USING OUTCROP-BASED GEOLOGICAL STRENGTH INDEX (GSI) SYSTEM A CASE STUDY IN KAYANGAN CATCHMENT, KULON PROGO REGENCY, YOGYAKARTA PROVINCE, INDONESIA - , Bagus Haryono, Dr. Danang Sri Hadmoko, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
In Indonesia that has tropical climate, landslide becomes one of damaging natural disasters. It causes disadvantages such as properties damages and victims of people. The occurence of landslide is very common due to intense rainfall, steep slope on the hilly or mountainous areas, and weak geological formations. Kayangan Catchment, Kulon Progo Regency, Yogyakarta Province, has weathered lihological formation, hilly and steeply sloped area that experiences the landslide occurrences. Due to the impact of landslide, disaster management must be done especially in providing the landslide hazard information. This data is very important to predict the probability of occurence and estimate the potential of losses. This research intends to find out landslide hazard zones of Kayangan Catchment based on deterministic method using outcrop-based Geological Strength Index (GSI) System. Deterministic method is one of the methods in landslide hazard zonation by means of slope stability analysis. This method uses safety factor (SF) with Mohr-Coulomb failure criteria as the basis in defining the susceptibility of an area. The equation of this criteria uses cohesion (c) and angle of friction (Î¦) as the parameters in calculation. Outcrop-based Geological Strength Index (GSI) system as the way to assess the characteristic of regolith in terms of lithology, surface condition (weathering) and discontinuity (blockiness) of rock mass was performed to obtain cohesion and friction angle data as the parameters used in slope stability assessment. In this research, it was performed by using Ilwis software. The results reveals the best accurate landslide hazard map shows moderate level of accuracy where the degree of fit (DF) in high hazard level = 54.86%, in moderate level = 44.28% and in low level = 0.86%. It shows a moderate performance of accuracy of landslide hazard map. Therefore the method can be considered reliable in landslide hazard zonation.